Evaluation of Reinforced Concrete Structural Performance under Earthquake Loads Based on Nonlinear Analysis in Lombok - Pratama, Ahmad Fauzan; Zameeruddin, Mohd. (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2024)
Lombok is located in a highly seismic region of Indonesia, where reinforced concrete (RC) buildings dominate the urban built environment. However, the seismic performance of existing RC structures varies significantly depending on design practice, material quality, and structural configuration. This study evaluates the seismic performance of reinforced concrete buildings in Lombok using nonlinear structural analysis, with emphasis on nonlinear static pushover and nonlinear dynamic time history methods. The study adopts a comparative analytical approach by synthesizing findings from recent experimental, numerical, and field-based studies related to RC seismic performance in Indonesia and other seismic regions. Key performance indicators such as interstory drift, plastic hinge formation, displacement capacity, and performance levels (Immediate Occupancy, Life Safety, and Collapse Prevention) are examined. The analysis highlights that many existing RC structures in Lombok are vulnerable to moderate-to-strong earthquakes due to low material strength, inadequate detailing, and non-compliance with modern seismic codes. However, structures designed with proper ductility provisions and evaluated using performance-based methods show satisfactory behavior under seismic loads. The study concludes that nonlinear analysis is essential for realistic seismic performance evaluation and recommends systematic assessment and retrofitting of existing buildings in Lombok to enhance structural resilience and reduce seismic risk.